1996
DOI: 10.1007/bf00227268
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanism of the post-activation depression of the H-reflex in human subjects

Abstract: It was demonstrated that the soleus H-reflex was depressed for more than 10 s following a preceding passive dorsiflexion of the ankle joint. This depression was caused by activation of large-diameter afferents with receptors located in the leg muscles, as an ischaemic block of large-diameter fibres just below the knee joint abolished the depression, whereas a similar block just proximal to the ankle joint was ineffective. The depression of the H-reflex was not caused by changes in motoneuronal excitability, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
382
4
4

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 405 publications
(409 citation statements)
references
References 30 publications
19
382
4
4
Order By: Relevance
“…None of these possibilities are mutually exclusive. Although it was suggested in the 1960s that PAD activates long loop reflexes (Taborikova and Sax 1969), later intracellular experiments suggested that this type of inhibition does not spread to other Ia fibers (Hultborn et al 1996). Regardless of the physiological reason for this phenomenon, we established normative data to compare with the pathological condition.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…None of these possibilities are mutually exclusive. Although it was suggested in the 1960s that PAD activates long loop reflexes (Taborikova and Sax 1969), later intracellular experiments suggested that this type of inhibition does not spread to other Ia fibers (Hultborn et al 1996). Regardless of the physiological reason for this phenomenon, we established normative data to compare with the pathological condition.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, PAD does not interfere with heteronymous sources to the motor pool (Beswick and Evanson 1957). Hultborn et al (1996) demonstrated that this presynaptic inhibitory mechanism is not accompanied by GABAergic primary afferent depolarization and does not produce dorsal root potentials. They also concluded that this inhibition does not spread to the motoneuron pool and is strictly confined to those Ia fibers that have been previously activated.…”
mentioning
confidence: 96%
“…Changes of such long duration have not previously been described. Postactivation depression is of longer duration than axo-axonal presynaptic inhibition but has still largely recovered in 10 s (Crone and Nielsen 1989;Hultborn et al 1996). Furthermore, this type of presynaptic depression is homosynaptic.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, postactivation homosynaptic depression of Ia afferents occurs with 18-Hz stimulation (e.g., Refs. 3,18), so this should markedly diminish reflex activation of the motoneurons by these afferents. Similar processes probably occur in other large-diameter afferents.…”
Section: Discussionmentioning
confidence: 99%